Reusable and efficient AA-co-PEOMA copolymer adsorbent for sustainable cationic dye mitigation from water - Bharti Saini; Aneri Patel (Sustainable Chemistry for Climate Action, 2025)
The present study entails insight into the fabrication of a novel copolymer (AA-co-PEOMA) adsorbent using varying proportions of both acrylic acid (AA) and poly(ethylene oxide) mono methacrylate (PEOMA) for the mitigation of potential crystal violet (CV) dye from wastewater adsorbents. The copolymer adsorbent consists of a large number of -COOH groups and flexible PEOMA chains, providing enhanced adsorption capability compared to traditional materials. The copolymer adsorbent is synthesized via free-radical polymerization and characterized by using Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The optimal adsorption conditions for CV dye are examined by adjusting various operational parameters such as the effect of pH, initial dye concentration, contact time, and temperature. The experimental results undergo additional analysis to align with multiple established kinetic and equilibrium isotherm models. The kinetics study inferred that the investigational data show a decent trend in line with the pseudo-second-order model. The adsorption of CV dye molecules on the synthesized copolymer mostly follows the Langmuir model, with the supreme adsorption capability (qmax) estimated to be 24.75 mg/g. Thermodynamic analysis confirmed the spontaneous and endothermic nature of the adsorption process. The reusability studies demonstrated sustainable performance over multiple cycles, and comparison of the proposed adsorbent with other potential adsorbents confirms the AA-co-PEOMA copolymer adsorbent's applicability for large-scale applications.